Gambaran Aktivitas Sebelum Tidur dan Kualitas Tidur Lansia Penderita Hipertensi - Khairatul Husnia; Reni Zulfitri; Arneliwati Arneliwati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Entering old age causes changes in various aspects, one of which is physiological, namely hypertension, which can affect the sleep quality of the elderly. This happens due to several factors, such as physical, spiritual, and other activities. The aim of this study was to determine the description of activities before bed and the sleep quality of elderly people with hypertension. This research uses a descriptive design. The sample used was 104 respondents, taken based on inclusion criteria using the snowball sampling technique. The research results indicate that the majority of hypertension sufferers were in the level 1 hypertension category, namely 74 respondents. The majority of elderly people's activities before going to bed for the physical dimension were 92 respondents, namely not stretching; the most for the spiritual activity dimension was doing dhikr with 89 respondents; and for other activities, the most was regulating the room temperature and avoiding disturbing sounds, namely 98 respondents. The majority of elderly people's sleep quality is poor, namely 78 respondents. The increasing number of activities before bed, whether physical, spiritual, or other, makes the sleep quality of the elderly poorer.